Effect of Cayratia trifolia Ethanol Extract on Bcl-2 expression and Apoptotic Cells in Dmba-induced Breast Cancer of Sprague Dawley Rats - I Ketut Sudiana (Journal of Global Pharma Technology, 2019)
The study aimed to clarify the effect of the administration of ethanol extract of Cayratia trifolia plants to breast cancer. This study was an experimental study using female animal model of Sprague Dawley rats, consisting of three groups, K0, the normal experimental animals, K1, the experimental animals with breast cancer receiving CMC 0.5%, and KP, experimental animals with breast cancer receiving ethanol extract of Cayratia trifolia in a dose of 300 mg/kgBW at 0.5% CMC.  The material to induce breast carcinoma formation was DMBA of 20 mg/kg in corn oil. The extraction of Cayratia trifolia plants used ethanol. The variables were the number of cells expressing Bcl-2 observed with immunohistochemical methods, and the number of cells undergoing apoptosis, which was observed using tunnel assay method. Statistical analysis was performed using ANOVA test. The number of cells expressing Bcl-2 and those undergoing apoptosis in breast cancer tissue between groups of animals receiving and not receiving ethanol extract of Cayratia trifolia showed significant difference (P<0.05). Oral administration of Cayratia trifolia ethanol extract has an effect on the decrease in the number of cells expressing Bcl2 and an increase in the number of cancer cells undergoing apoptosis.Keywords: Breast carcinoma; Proto-oncogene; Tumor suppressor gene; Cayratia trifolia.